The Effect of Customer-Based Brand Equity (CBBE) Model on Perceived Brand Equity of Sabah SMEs Food Brands - Masrun, Sharinee; Albert Gisip, Imelda; Sumin, Viduriati; Harun, Amran (Penerbit UTHM, 2020)
In Malaysia, SMEs mainly face major difficulties in innovating and transforming their organisations into Industry 4.0. They have to use the cash in wages and advertising (Allaudeen, 2018). She adds inadequate marketing and branding resources (53%) and elevated branding costs (52%) have disclosed a fresh study to the most Malaysian SMEs. In Malaysia, the primary problem facing small and medium-sized enterprises is the lack of knowledge of marketing technology, branding, customer loyalty (Lau, 2017). The main concern of tiny and medium-sized companies (SMEs) is the maintenance of sales and profit margins, according to a latest national study of CTOS customer base companies (Sunbiz, 2019).